Impact of Subthalamic Deep Brain Stimulation on Impulse Control Disorders in Parkinson's Disease: A Prospective Study. Issue 3 (6th October 2020) - Santin, Marie des Neiges; Voulleminot, Paul; Vrillon, Agathe; Hainque, Elodie; Béreau, Matthieu; Lagha‐Boukbiza, Ouhaid; Wirth, Thomas; Montaut, Solveig; Bardinet, Eric; Kyheng, Maeva; Rolland, Anne‐Sophie; Voirin, Jimmy; et al.
ABSTRACT: Background: Impact of subthalamic deep brain stimulation (DBS) on impulse control disorders (ICD) in Parkinson's disease (PD) remains controversial. Objectives: The objectives of this study were to analyze the natural history of ICD between baseline and 1 year after subthalamic DBS in patients with PD and to identify predictive factors, taking into account the positions of the active contact and stimulation parameters. Methods: We analyzed postoperative modifications of ICD based on the multicentric, prospective Predictive Factors and Subthalamic Stimulation in Parkinson's Disease cohort. ICD status and Ardouin Scale of Behaviour in PD were assessed at baseline and 1 year following subthalamic DBS. Location of active contacts within the 3 subthalamic nucleus functional territories was investigated. Results: A total of 217 were patients included. Of the patients, 10.6% had ICD at baseline of which 95.6% improved at 1 year following subthalamic DBS; 3.6% of the patients experienced de novo ICD at 1 year following subthalamic DBS. Dopamine agonist dose reduction (from 309.8 to 109.3 mg) was the main driver of ICD regression ( P = 0.05). Higher preoperative dyskinesias were associated with poorer ICD evolution ( P = 0.04). Whereas baseline apathy was a risk factor of de novo ICD ( P = 0.02), ICD improvement correlated with postoperative apathy ( P = 0.004). Stimulation power and position of active contacts—mainly located within the sensorimotor part of the subthalamic nucleus—did not influence ICD. Conclusions: This 1‐year, postoperative follow‐up study showed ICD regression and dopaminergic drug reduction with optimal position of the active contacts within the subthalamic nucleus. Whereas patients with PD with preoperative ICD were prone to postoperative apathy, we also showed that those with preoperative apathy had a higher risk to experience postoperative de novo ICD, further highlighting the meaningful influence of postoperative management of dopaminergic medication on outcome and the continuum between apathy and ICD. © 2020 International Parkinson and Movement Disorder Society